Fibroblast growth factor 23 is associated with the development of gestational diabetes mellitus: research article - Hocher, Carl-Friedrich; Chen, Xin; Zuo, Jiao; Horvathova, Katarina; Hocher, Berthold; Krämer, Bernhard; Chu, Chang (Diabetes, metabolism research and reviews, 2023)
Background Besides its established impact on bone and mineral metabolism, it was suggested that fibroblast growth factor 23 (FGF23) might play an important role in the pathogenesis of type 2 diabetes. The impact of FGF23 on gestational diabetes mellitus (GDM), however, is not well understood. iFGF23 ELISAs measure the intact FGF23 molecule, whereas cFGF23 assays measure intact FGF23 as well as degradation products of FGF23. Objectives The aim of this study is to compare the association of maternal and foetal cFGF23 and iFGF23 with GDM in a German birth cohort. Methods cFGF23 and iFGF23 were analysed in 826 random mother/child pairs from the Berlin Birth Cohort. Results Mothers who developed GDM had higher concentrations of iFGF-23 compared to mothers who did not suffer from GDM (19.73 vs. 13.23 pg/mL, p < 0.0001), but not higher concentrations of cFGF-23. Multivariant regression analyses showed that gestational diabetes is associated with iFGF23 independently of confounding factors such as age, BMI, ethnic background, family history of diabetes, smoking during pregnancy, and recurrent pregnancy loss. This, however, was only seen when using an iFGF23 ELISA measuring just the full length FGF23 and not in addition FGF23 fragments. No differences in both iFGF23 and cFGF23 concentrations between the GDM and non-GDM groups were detected in cord blood samples of the offspring. Conclusions This study of a representative German birth cohort showed that maternal but not foetal iFGF23 is independently associated with GDM.
Gesehen am 06.02.2024